An impedance study of the adsorption of nucleic acid bases at glassy carbon electrodes - Oliveira-Brett, A. M. (2002)
Electrochemical impedance has been used to study the adsorption at glassy carbon electrodes of guanine, its corresponding nucleoside, guanosine, and adenine. Impedance studies at different concentrations and applied potentials show clearly that all three bases are adsorbed on the electrode, blocking the surface. Irradiating the electrode with low-frequency (20 kHz) ultrasound whilst recording the impedance spectra increased transport of molecules to the electrode surface with cavitation cleaning the surface and removing strongly adsorbed molecules of bases. In this way, sonoelectrochemical experiments enabled the electrode processes to be studied in the absence of adsorption.